2018
DOI: 10.1111/scs.12572
|View full text |Cite
|
Sign up to set email alerts
|

Correlate of burden and coping ability of caregivers of older adults with chronic illness in Nigeria

Abstract: This study concluded that caregiving activities impose a severe burden on the caregivers. Religion was the most used, and coping ability is predicted by burden and religion. Therefore, healthcare providers should consider interventions to promote the use of effective coping skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
0
14
0
3
Order By: Relevance
“…This is consistent with the findings of a study conducted by (53) in the United States of America, which revealed that more than two-fifths of caregivers reported a high level of burden, more than one-third reported a medium level of burden, and more than onefifth reported a low level of caregiver burden. It was also endorsed by the study of (54) conducted in Nigeria who stated in his study that less than two-fifths of his study sample experienced severe burden, more than one-quarter of his study sample experienced moderate burden, and more than one-tenth of his study participants recorded a low level of burden. Also, it was supported by the study of (55) conducted in Egypt who illustrated that more than twofifths of their study sample reported a high and a moderate level of burden and more than one -fifth of the study participants reported a low level of burden.…”
Section: Discussionmentioning
confidence: 91%
“…This is consistent with the findings of a study conducted by (53) in the United States of America, which revealed that more than two-fifths of caregivers reported a high level of burden, more than one-third reported a medium level of burden, and more than onefifth reported a low level of caregiver burden. It was also endorsed by the study of (54) conducted in Nigeria who stated in his study that less than two-fifths of his study sample experienced severe burden, more than one-quarter of his study sample experienced moderate burden, and more than one-tenth of his study participants recorded a low level of burden. Also, it was supported by the study of (55) conducted in Egypt who illustrated that more than twofifths of their study sample reported a high and a moderate level of burden and more than one -fifth of the study participants reported a low level of burden.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies in the sub-Saharan ( Dotchin et al, 2014 and Mugisha et al, 2013 ) as well Nigerian studies on caregiving have focused on specific illness conditions especially mental illness ( Adeosun, 2013 and Jack‐Ide, Uys, & Middleton, 2013 ) and ( Yusuf, Nuhu, & Akinbiyi, 2009 ) older adults with hip fracture ( Diameta et al, 2018 ), cancer ( Akpan-Idiok & Anarado, 2014 ), and patients with End-Stage Renal Disease ( Oyegbile & Brysiewicz, 2017 ). Similarly, Faronbi (2018) and Faronbi and Olaogun (2017) quantitatively examined the burden of caregiving for older adults chronic illness. Despite all these arrays of studies, little information exists that qualitatively examines caregivers’ burden among caregivers of older adults with chronic illness from most low-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies observed the interrelationship between coping, caregiver burden, and AG. [ 14 21 46 ] Thus, the relationship between the three needs to be confirmed by further research.…”
Section: Discussionmentioning
confidence: 99%